2017
DOI: 10.1590/0103-8478cr20160277
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise on serum electrolytes and acid base balance in Mangalarga Marchador horses submitted to cavalcade of 4, 8 and 20km

Abstract: INTRODUTIONPhysical exercise is responsible for alterations in various blood parameters (KIENZLE et al., 2006). Biochemical (TOLEDO et al., 2001), hydroelectrolytic (DI FILIPPO et al., 2009;, hormonal and metabolic (NOLETO et al., 2016) changes have been described in horses submitted to exercise of different intensities and durations. These changes occur as the organism attempts to adapt and supply the increased metabolic demand triggered by physical effort (PICCIONE et al., 2007) and are under most circumstan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
4
0
1
Order By: Relevance
“…Decrease in pH, HCO 3 and cBase with concomitant reduction in pCO 2 reinforced the occurrence of metabolic acidosis in the present study, corroborating the studies by SILVA et al (2009) who also reported decrease in these parameters in the venous blood of horses after submitting them to maximum exercise on a treadmill. The decrease in these parameters reaffirms the effect of lactic acid diffusion in the blood originating from the muscle cells under the predominance of the anaerobic glucose metabolism, causing lactic acidosis (MARLIN & NANKERVIS, 2002;BARBOSA et al, 2016;LINHARES et al, 2017).…”
Section: Time -------------------------------------------------------mentioning
confidence: 73%
See 1 more Smart Citation
“…Decrease in pH, HCO 3 and cBase with concomitant reduction in pCO 2 reinforced the occurrence of metabolic acidosis in the present study, corroborating the studies by SILVA et al (2009) who also reported decrease in these parameters in the venous blood of horses after submitting them to maximum exercise on a treadmill. The decrease in these parameters reaffirms the effect of lactic acid diffusion in the blood originating from the muscle cells under the predominance of the anaerobic glucose metabolism, causing lactic acidosis (MARLIN & NANKERVIS, 2002;BARBOSA et al, 2016;LINHARES et al, 2017).…”
Section: Time -------------------------------------------------------mentioning
confidence: 73%
“…The reduction in the HCO 3 concentration was due to the need of buffering by these increased H + protons (MARLIN & NANKERVIS, 2002), justifying their reduction at T1 and without full recomposition to normal concentrations in T2, which lowered the pH at T2 (Table 1). Decrease in cBase at T1 (P<0.05) may have occurred due to the reduction of HCO 3 -, because this is the most quantitative and important H + buffer in the organism (CARLOTTI, 2012), confirming that the variation in the cBase can accompany the HCO 3 direction variation in horses after exercise (KUPCZYNSKI e SPITALNIAK, 2015;LINHARES et al, 2017).…”
Section: Time -------------------------------------------------------mentioning
confidence: 90%
“…(Table 3). This decrease occurred because, besides using the HCO3̄ to buffer the increase in H + prótons, the organism also requires bigger carbon dioxide elimination (CO2) from the body, reducing the pCO2, and base actions that reduce the pCO2 and body cBase value, to control the metabolic acidosis, confirming that the CBase value can accompany the direction of HCO3̄ in horses after exercise (LINHARES et al, 2017). Due to this, the cBase also decreased in the horses after concluding three sprints, CBase or base excess (EB) represents the base accumulation or nonvolatile acid in the blood, excluding the plasma HCO3̄ and the hemoglobin concentration in the blood (LIDINGER and WALLER, 2008).…”
Section: Resultsmentioning
confidence: 90%
“…Another study found a sudden upsurge of lactate concentration after 15 min of recovery [ 49 ]. The horses with high lactate concentrations showed better results than those with low lactate levels, indicating that other mechanisms may be involved in the regulation of blood lactate concentration [ 50 ]. Nevertheless, postrace blood lactate concentrations were higher than pre-race ones for all horses; however, they were elevated more in the Arabian horses than in the Žemaitukai breed, probably owing to the significantly higher anaerobic capacity in the Arabian horses.…”
Section: Discussionmentioning
confidence: 99%